The Economics of Moonlighting: A Double Self-Selection Model - Krishnan, Pramila (The Review of Economics and Statistics, 1990)
The model proposed here for obtaining the labor supply functions of moonlighters uses a double self-selection system to explore the husband's decision to moonlight together with his wife's decision to work. Subsequently, the labor functions are classified under two regimes depending on whether the wife works. The model is estimated based on a cross-section of 4, 448 married couples from the Survey of Income and Program Participation, Wave 2. I find that the household production time of husbands and wives are substitutes and that specific human capital deters moonlighting. Copyright 1990 by MIT Press.